Effects of age of Awassi ewes crossed with Hamdani rams on reproductive and wool characteristics - Hussein, Dalaf Ali (Universitas Airlangga, 2025)
This study was conducted in Al-Taji District, north of Baghdad, Iraq, on a privately managed sheep farm specializing in animal breeding. The objective was to evaluate the impact of ewe age on wool characteristics and reproductive performance in hybrid sheep produced by crossing Awassi ewes (n= 70) with Hamdani rams (n= 17). Records from the sires (Hamdani rams, originally from Mosul) and dams (Awassi ewes from Baghdad) were used. Reproductive data were first analyzed, including litter size and sex ratio. The total number of lambs born was 90, comprising 50 males and 40 females, with respective percentages of 55.6% and 44.4%. The Chi-square (χ²) value was 4.50, indicating a significant difference at the p ≤0.05 level. The mean litter size was 1.30 lambs per ewe, which was not statistically significant. Wool characteristics were measured in a subset of 43 ewes, distributed across age groups ranging from 1.5 to 5 years, with 5 animals per group. Significant differences (p ≤0.05) were observed in raw fleece weight, with the highest average (2,234 g) recorded in 3.5-year-old ewes. Clean fleece weight also differed significantly (p ≤0.05), with the highest value (2,060 g) found in 2-year-old ewes. However, no significant differences were recorded for fiber length or fiber diameter.